Analisis Kelayakan Usaha Revitalisasi Rice Milling Plant (RMP) di Desa Wonosari Kecamatan Mesuji Timur Kabupaten Mesuji - Apriyanto, Arif; Abidin, Zainal; Rupaidah, Erlina (Universitas Batangahari Jambi, 2024)
This study aims to analyze the feasibility of revitalizing the Rice Milling Plant (RMP) in Wonosari Village, Mesuji Timur District, Mesuji Regency, considering existing conditions, expenditures, revenues, and financial and non-financial engineering strategies. Through comprehensive data collection and in-depth financial analysis, this study identifies challenges faced by RMP, including infrastructure requiring updates, suboptimal management, and fluctuating raw material prices influenced by global economic conditions. The findings indicate that, under current conditions, RMP is financially infeasible based on indicators such as Net Present Value (NPV), Gross Benefit-Cost Ratio (Gross B/C), Net Benefit-Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback Period (PP). However, with the implementation of a series of engineering strategies including production optimization, infrastructure improvement, product quality enhancement, and effective marketing strategies, RMP can achieve business feasibility. Sensitivity analysis confirms the importance of strategic adaptation to changes in raw material and product prices. This study concludes that the revitalization of RMP requires a holistic approach integrating financial, operational, and marketing aspects to create a viable business and support local economic development. The success of revitalization efforts will heavily depend on synergistic cooperation between the government, the private sector, and the farming community